Organização e dinâmica familiar no contexto do paciente oncológico - Fialho, Roberta Barreira Massler (2003)
The family unit is an integrated and dynamic. Once the diagnosis of cancer, studies point to the emergence of crises in the primary group, which undergoes a restructuring. This study aimed to understand the family dynamics of cancer patients from the disclosure of diagnosis and the role of family in the context of the disease. We analyzed the impact of cancer diagnosis in family roles, the emotional bonds, in the styles of interpersonal communication. We conducted a qualitative study of four cases of patients with cancer. The care of these patients was conducted at the Cancer Institute of Ceará and Life House, located in Fortaleza, Ceara, where he performed the data collection. Initially, we analyzed the records of patients pre-selected. Then was given informed consent and were interviewed from a semi-structured with patients and their family members. In parallel, we designed a field journal to complement the information. The interviews were taped and transcribed. The content of the interviews identified the units of meanings attributed to the experience of illness by the patient and the components of the families interviewed, as well as identify changes in familial roles of members, the emotional ties and ways of communication revealing the impact of cancer diagnosis . The narratives indicate changes in roles and in some cases, the inclusion of others in the family context. There was the expulsion of some members of the family and approach of other components further apart, indicating changes in the affective bonds, forms of communication, transforming the family dynamics before the diagnosis. It was also observed that the family can not always give emotional support to patients, it is he who gives emotional support to their. The study indicates that family dynamics dimensions involves physical, psychological, social, environmental and cultural. The family, along with the patient, too ill, each member in his own way, making it necessary to be able to deal better with the trajectory of the disease that the patient suffers, thus favoring the reduction of the stress caused by cancer. With regard to family roles, the study points to a transformation at least momentarily. The emotional ties can be strengthened or weakened. The styles of interpersonal communication also become sayings and unspoken or secrets.